KANDUNGAN KIMIA BIOMASA DAN KOMPOS DARI TUMBUHAN AIR KIAPU (Pistisia statiotes L.) YANG TUMBUH DI KAMPUNG WASUR, KABUPATEN MERAUKE - Wahida Wahida; Yosefina Mangera; Irianis Luky Latuperisa (Universitas Musamus, Merauke, Papua, 2013)
This study aims to determine the chemical content of biomass and compost of the aquatic plants (Pistia stratiotes L.) at the Wasur village, Merauke. Benefits to be gained by the study is obtaining information about the content of the proximate and organic matter of Pistia plants at the Wasur village, so the function can be optimized. The results of chemical content of biomass and compost Pistia showed that plants have the potential to be used as feed additives for monogastric livestock, especially cattle as well as additional materials for composting.